Analisis dan Perancangan Sistem Informasi Pelaporan Pendataan Keluarga Berencana Kabupaten Jombang Pada Dinas Pengendalian Penduduk dan Keluarga Berencana Kabupaten Jombang - Dwi Lis Mardiana; Ismiarta Aknuranda; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Office of Population and Family Planning Control (DPPKB) Jombang District have a duty to run a program of Family Planning services in Jombang, which is assisted by the Family Planning Field Officers (PLKB). PLKB is responsible for data collection on family planning in every sub-district every month. However, the reporting process was manually, as a result, the process of recording the report is also hampered while the report must be sent to The National Population and Family Planning before the 15th of each month and when it is late DPPKB Jombang district will be marked red and this affects the evaluation of the official performance appraisal. If viewed from the above problems, it required analysis and design of information systems of reporting family planning data collection that can improve the efficiency of the reporting process. In this study, the stages of analysis and design of information systems using Object Oriented Analysis and Design (OOAD) approach and consistency design evaluation in the form of Requirements Configuration Structure and Decision table. This study resulted in the current business process model and the proposal, the list of user needs, features, list of system requirements, use case modeling, system design and consistency evaluation. Evaluation of the consistency from defining requirements generate value requirement consistency index (RCI) of 100%, which means defining the needs of the system is consistent and for evaluation of the consistency of the design artifacts lead to the conclusion that the artifact has been a consistent system design.